Juvenile social status predicts primary sex allocation in a sex changing fish. Issue 4 (July 2016) - Solomon‐Lane, Tessa K.; Shvidkaya, Polina; Thomas, Alma; Williams, Megan M.; Rhyne, Andrew; Rogers, Lock; Grober, Matthew S.
SUMMARY: Both individual sex and population sex ratio can affect lifetime reproductive success. As a result, multiple mechanisms have evolved to regulate sexual phenotype, including adult sex change in fishes. While adult sex change is typically socially regulated, few studies focus on the non‐chromosomal mechanisms regulating primary sex allocation. We investigated primary sex determination in the bluebanded goby ( Lythrypnus dalli ), a bidirectionally sex‐changing fish. Of the studies investigating primary sex determination in species with adult sex change, this is the first to incorporate the roles of social status and size, key factors for determining adult sex allocation. For L. dalli, adult sex is regulated by social status: dominants are male; subordinates are female. In social groups of laboratory‐reared juveniles, we demonstrate that status also predicts primary sex. Dominant juveniles developed male‐typical genitalia, and their gonads contained significantly less ovarian tissue than subordinates, which developed female‐typical genitalia. To better understand natural development, we quantified the distribution of juveniles and adults on the reef and analyzed genital papilla and gonad morphology in a sample of wild‐caught juveniles. Juveniles were observed in various social environments, and most grouped with other juveniles and/or adults. The majority of field‐caught juveniles had female‐typical genitalia and bisexual, female‐biased gonads. These data are consistent with a single mechanism that regulates sexual phenotype throughout life. Social status could first cause and then maintain through adulthood a female‐biased population, allowing individuals to regulate sex based on local conditions, which is important for optimizing lifetime reproductive success.